Dampak Covid-19 terhadap semangat belajar siswa - Az-Zahra, Maulany (Maliki Interdisciplinary Journal, 2024)
Enthusiasm is a strong feeling in a person so that he can build, turn on a desire and then achieve that desire. The spirit of learning must be instilled in every student so that students do not give up easily. The purpose of this journal is to find out how the impact of Covid-19 has on students' enthusiasm for learning, with various learning methods in the Covid-19 era. The method used in this journal is a literature review from various journals and books and it is concluded that there is a decrease in student enthusiasm for learning after the Covid-19 pandemic with various inhibiting and encouraging factors.